Counting in the rain: questions about traffic source analysis on library websites - Urbano, Cristóbal (Anuario ThinkEPI, 2009)
Strategic reflections on analysis of traffic sources for library websites. In an environment where search engine optimisation, exposure to the social web and visitor loyalty become prominent features in web analytics metrics, there is a need for a benchmark with commercial sites to adjust good practises in metrics for library websites. The transition that libraries are making to digital services and resources requires taking note of web analytics strategy, marketing, search engine optimisation, links exchange, and loyalty policy, well-developed in commercial websites.
Keywords: Web analytics; Library statistics; Library websites; Social web.